Socioeconomic disadvantage and human papillomavirus (HPV) vaccination uptake. Issue 3 (24th January 2022) - Kurani, Shaheen; MacLaughlin, Kathy L.; Jacobson, Robert M.; St. Sauver, Jennifer L.; Jenkins, Gregory D.; Fan, Chun; Jacobson, Debra J.; Inselman, Jonathan; Zhu, Xuan; Griffin, Joan M.; Finney Rutten, Lila J.
Highlights: Human papillomavirus (HPV) vaccination uptake remains low in the U.S. Adolescents from disadvantaged areas are less likely to initiate and complete HPV vaccination. This calls for focused attention on resource allocation and social determinants. Abstract: Importance: Despite availability of safe and effective human papillomavirus (HPV) vaccines, vaccination uptake remains low in the U.S. Research examining the impact of neighborhood socioeconomic status on HPV vaccination may help target interventions. Objective: To examine the association between area deprivation and HPV vaccine initiation and completion. Design, setting, participants: Retrospective cohort study of individuals aged 11–18 years residing in the upper Midwest region. Receipt of HPV vaccination was examined over a three-year follow-up period (01/01/2016–12/31/2018). Main outcomes and measures: Outcomes of interest were initiation and completion of HPV vaccination. Demographic data were collected from the Rochester Epidemiology Project (REP). Area-level socioeconomic disadvantage was measured by calculating an Area Deprivation Index (ADI) score for each person, a measure of socioeconomic disadvantage derived from American Community Survey data. Multivariable mixed effect Cox proportional hazards models were used to examine the association of ADI quartiles (Q1-Q4) with HPV vaccine series initiation and completion, given initiation. Results: Individuals residing in census block groups with higher deprivation had significantly lower likelihood of HPV vaccine initiation (Q2: HR = 0.91, 0.84–0.99 Q3: HR = 0.83, 0.76–0.90; Q4: HR = 0.84, 0.74–0.96) relative to those in the least-deprived block groups (Q1). Similarly, those living in block groups with higher deprivation had significantly lower likelihood of completion (Q2: HR = 0.91, 0.86–0.97; Q3: HR = 0.87, 0.81–0.94; Q4: HR = 0.82, 0.74–0.92) compared to individuals in the least-deprived block groups (Q1). Conclusions and relevance: Lower probability of both HPV vaccine-series initiation and completion were observed in areas with greater deprivation. Our results can inform allocation of resources to increase HPV vaccination rates in our primary care practice and provide an example of leveraging public data to inform similar efforts across diverse health systems.